Transportation mobility management - Sarhan M. Musa (19794273) (2015)
Today, the world has observed a remarkable growth in the use of transportation mobile communications for road safety. While a user in a vehicle moves to a new communication cell, a wireless terminal requests a handoff for new channel in the new cell. Due to that movement, some of the challenges issues are developed such as, the increase in traffic volumes and demand for high speed transportation mobile communications call for fast, seamless and high performance handoff in mobile communications network. When a wireless user in a vehicle moves from one base station cell to another, handoff protocols reroute the existing active connections in the new transportation cell. The future challenges in next generation high speed transportation mobile networks are to minimize the packet loss and to provide efficient use of the network resources while maintaining quality of service assurances. Therefore, the performance of efficient management and a successful handoff operation in transportation mobile networks become an important issue for road safety traffic. This work shows analytical handoff management for transportation users in a high speed mobile communications network. We demonstrate the performance of handoffs with mobility consideration using several metrics including the alteration of states prior to reaching a transportation mobility cell boundary, the speed of transportation mobile terminal, and the distance between a transportation mobile terminal and a transportation cell boundary. We illustrate the performance evaluation for the factor of transportation mobility with taking into account the high speed status of a mobile vehicle user. Numerical results of the transportation performance analysis and the probability of requiring a handoff are demonstrated using Maple. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.55